Mode-locked bismuth-based erbium-doped fiber laser with stable and clean femtosecond pulses output - Harun, Sulaiman Wadi; Akbari, Reza; Arof, Hamzah; Ahmad, Harith (IOP Publishing, 2011)
A passively mode-locked fiber ring laser is demonstrated using a 49 cm long bismuth oxide based erbium-doped fiber (Bi-EDF) and a fast semiconductor saturable absorber. Stable and clean short pulses are achieved because of these short and high nonlinear characteristics of the Bi-EDF. The laser operates at 1560 nm with a repetition rate of 8.3 MHz and a center wavelength of 1560 nm. The calibrated auto-correlator pulse trace of the laser shows a sech2 pulse shape, with an estimated pulse width of 340 fs.